EVALUATION STUDY OF BLAST-INDUCED ROCK FRAGMENTATION USING STEMROCK AND BLASTBAG AIR DECK SYSTEMS WITH THE KUZ-RAM METHOD AT THE LIMESTONE QUARRY NAROGONG SITE OF PT SOLUSI BANGUN INDONESIA TBK - Cahyaningsih, Bimbi; Putra, Arahman Panji; Harsono, Dimas Ghani Putra; Avesina, Victor Habib (Jurnal Sains dan Teknologi Reaksi, 2025)
PT Solusi Bangun Indonesia Tbk (SBI) has implemented air-deck technology in limestone blasting to optimize explosive consumption while maintaining the required fragmentation quality. This study aims to evaluate and compare the performance of two types of air-deck systems, namely stemrock and blastbag, in producing suitable rock fragmentation at the Sijebi Quarry, Narogong. The research was conducted through three blasting trials with geometry design based on ICI Explosives guidelines and fragmentation prediction using the Kuz-Ram model. The blasting parameters evaluated included burden, spacing, stemming, subdrilling, and charge column length. The results indicate that stemrock air-deck with a 7.5 m primer charge produced 87.12% of fragments smaller than 50 cm, whereas blastbag air-deck under the same conditions achieved 95.31%. However, other trials using blastbag produced coarser fragmentation with fragments exceeding 100 cm. Overall, the most reliable fragmentation distribution, closely aligned with Kuz-Ram predictions, was obtained with a blasting geometry of 4 m burden, 5 m spacing, 3 m stemming, 1 m subdrilling, and a 7.5 m primer charge using ANFO in limestone. This study recommends the aforementioned blasting geometry as the optimal configuration for achieving efficient and effective fragmentation in limestone quarry operations. Keywords: Air Deck, Stemrock, Blastbag, Fragmentation, Kuz-Ram.